Pulse and logic circuits - Gillie, Angelo C. ([S.l.] : McGraw-Hill, 1968)
This book is designed to provide a comprehensive treatment of pulse and logic circuit fundamentals. The material in this book falls in 3 categories: 1. Passive pulse circuitry 2. Switching Circuitry 3. Matrix, counting, and register circuits. Non-sinusodial waveforms form one of the foundations for much of the material treated here. The basic waveforms of the.....
Import.